Agrarian Legal Politics of the Special Region of Yogyakarta in the Indonesian Legal System A Study on Law No 13 of 2012 - Jamaluddin Mahasari (Journal of Law, Politic and Humanities, 2025)
This study examines agrarian legal politics in the Special Region of Yogyakarta (DIY) within the Indonesian legal system, focusing on Law Number 13 of 2012 on the Special Status of DIY. The research analyzes the dynamics of agrarian law in DIY, which is unique due to the coexistence of two legal systems: the national law based on the Basic Agrarian Law (UUPA) and the traditional royal agrarian system. The comparison between agrarian legal politics in DIY and national policies reveals significant differences in land law implementation, particularly in the aspects of land inventory, certification, and the legal status of Sultanate and Kadipaten (Duchy) lands. The main challenges identified include the lack of adequate baseline data, community land ownership without legal certainty, and regulatory inconsistencies regarding the management of village land and Sultanate/Duchy lands. Additionally, the disharmony between national agrarian policies and the agrarian legal politics of DIY poses further challenges, especially regarding land ownership and land-use rights for non-indigenous Indonesian citizens. This study recommends a reconstruction of agrarian legal policies at both the national and DIY levels through the revision of regulations such as Law Number 13 of 2012, Government Regulation Number 38 of 1963, and Government Regulation Number 24 of 1997. A more equitable and harmonized approach to the agrarian legal system is essential to ensure legal certainty, social welfare, and alignment between national policies and the special status of DIY.